2017
DOI: 10.1111/rda.12980
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the BioPRYN enzyme‐linked immunosorbent assay for detection of pregnancy‐specific protein‐B (PSPB) and diagnosis of pregnancy in American bison (Bison bison)

Abstract: This study assessed the accuracy of the commercial BioPRYN ELISA for the detection of pregnancy-specific protein-B (PSPB) using a single blood sample to determine pregnancy status in American bison (Bison bison). A total of 49 bison cows were used in the study, and sampled at two time-points during the gestation period, fall and spring, correlating with early- to mid-term gestation (average 62.9 days post-mating) and mid- to late-term gestation (average 229.2 days post-mating), respectively. Sensitivity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…In 2 and 3TP, PAG concentrations were dramatically below those observed at peak in dairy cows [32] , but were similar to those observed in Water Buffaloes [30] . Total PAG concentrations observed in our study during the 2 last trimesters of American Bison pregnancies were above those observed with the specific PSPB assay in mid and late gestation [6] , conversely to the observations in 1TP. In the present cohort of American Bison, like in Water Buffaloes [30] , no PAG peak was observed during the 2 last trimesters of pregnancy.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…In 2 and 3TP, PAG concentrations were dramatically below those observed at peak in dairy cows [32] , but were similar to those observed in Water Buffaloes [30] . Total PAG concentrations observed in our study during the 2 last trimesters of American Bison pregnancies were above those observed with the specific PSPB assay in mid and late gestation [6] , conversely to the observations in 1TP. In the present cohort of American Bison, like in Water Buffaloes [30] , no PAG peak was observed during the 2 last trimesters of pregnancy.…”
Section: Discussionsupporting
confidence: 64%
“…In the present report, a transient peak could have been missed, due to the limited data available in 1TP. An assay for a specific glycoprotein of the PAG family, the PSPB [13] , has been validated in American Bison [6] and showed higher concentration (1.42 ± 1.29ng/mL) in early pregnancy (0-45 d) than our total PAG assay. Despite our caprine PAG RIA kit showed the best detection of the American Bison PAG epitopes, the different sensitivities of the assays could explain those diverging results.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations